2018
DOI: 10.1002/tht3.271
|View full text |Cite
|
Sign up to set email alerts
|

Proving that the Mind Is Not a Machine?

Abstract: This piece continues the tradition of arguments by John Lucas, Roger Penrose and others to the effect that the human mind is not a machine. Kurt Gödel thought that the intensional paradoxes stand in the way of proving that the mind is not a machine. According to Gödel, a successful proof that the mind is not a machine would require a solution to the intensional paradoxes. We provide what might seem to be a partial vindication of Gödel and show that if a particular solution to the intensional paradoxes is adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Penrose wasn't careful in calibrating the exact list of principles of truth employed in the argument. This task has been recently taken up by logicians and philosophers (Koellner, 2018;Stern, 2018). In particular, Stern analyzes Penrose's argument by formalizing it in KF + CONS: he shows that mechanism can be refuted in KF + CONS, although this refutation cannot fall into the extension of the truth predicate of KF + CONS (as we have seen, this pattern is quite common in KF + CONS).…”
Section: Truth As a Logico-mathematical Toolmentioning
confidence: 92%
“…Penrose wasn't careful in calibrating the exact list of principles of truth employed in the argument. This task has been recently taken up by logicians and philosophers (Koellner, 2018;Stern, 2018). In particular, Stern analyzes Penrose's argument by formalizing it in KF + CONS: he shows that mechanism can be refuted in KF + CONS, although this refutation cannot fall into the extension of the truth predicate of KF + CONS (as we have seen, this pattern is quite common in KF + CONS).…”
Section: Truth As a Logico-mathematical Toolmentioning
confidence: 92%
“…This theory is philosophically indeed remarkably strong. Stern has recently shown that this theory proves the elusive conclusion of the Lucas‐Penrose argument, i.e., that the human mind is not a formal system [Stern 2018]. Yet Stern (rightly) does not in any way take this argument as a justification of the conclusion that the mind is not a Turing machine.…”
Section: The Justificatory Role Of Truthmentioning
confidence: 99%
“…In Stern, , the grant number for the Marie Sklodowska‐Curie Individual Fellowship was published with error in the Acknowledgments.…”
mentioning
confidence: 99%